Evaluation and Management of Genitourinary Emergencies in Patients with Cancer - Demis N. Lipe; Phillip B. Mann; Rodrick Babakhanlou; Maria T. Cruz Carreras; A. Guido Hita; Monica K. Wattana (Emergency Medicine International)
Background. Genitourinary emergencies in cancer patients are common. Most cancer treatments are administered in the outpatient setting, and patients with complications often visit the emergency department. However, there is no recent emergency medicine literature review focusing on genitourinary emergencies in the oncologic population. Objective of the review. To increase awareness of common genitourinary emergencies in patients with cancer and enable the prompt recognition and appropriate management of these conditions. Discussion. Genitourinary emergencies in patients with cancer require a multidisciplinary approach to treatment. The most common genitourinary emergencies in patients with cancer are related to infection, obstructive uropathy, hemorrhagic cystitis, and complications associated with urinary diversions. The treatment approach in patients with infections, including viral infections, is similar to those without cancer. Understanding the changes in the anatomy of patients with urinary diversions or fistulas can help with the management of genitourinary emergencies. Conclusions. Familiarization with the uniqueness of genitourinary emergencies in patients with cancer is important for emergency physicians.